1982
DOI: 10.1007/bf02019714
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of amoxicillin, potassium clavulanate and their combination

Abstract: Pharmacokinetic parameters after oral administration of 500 mg amoxicillin, 125 mg potassium clavulanate and 625 mg of their combination (augmentin) were determined in a randomized crossover study in ten healthy volunteers. The absolute bioavailability of amoxicillin (AUCoral/AUCi.v.) was 0.70 +/- 0.12. The mean maximum serum concentration of amoxicillin was 6.5 +/- 1.6 mg/l after administration alone and 6.5 +/- 1.4 mg/l after administration in combination. The respective values for potassium clavulanate were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Serum amoxicillin concentration found in this study is comparable to levels previously reported [18][19][20][21]; however, what is remarkable here is the high prevalence of children with low plasma levels. Although delays in collecting blood samples cannot be excluded, we ascribe it to a low compliance of the patient to the chemoprophylaxis protocol (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Serum amoxicillin concentration found in this study is comparable to levels previously reported [18][19][20][21]; however, what is remarkable here is the high prevalence of children with low plasma levels. Although delays in collecting blood samples cannot be excluded, we ascribe it to a low compliance of the patient to the chemoprophylaxis protocol (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Department of ''Amedeo Avogadro'' University of Eastern Piedmont in Novara for elective tonsillectomy. All tonsils were removed by cold dissection tonsillectomy, with a mean surgery time of 20 min (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Previously, patients were treated with 3 doses of amoxicillinclavulanic acid given orally the day before plus a further dose given 2 h before admittance into the operating theatre.…”
Section: Subjects and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of amoxicillin in combination with clavulanic acid does not influence the absorption of either drug (52). Furthermore, the bioavailability was not affected by food (16).…”
Section: Discussionmentioning
confidence: 99%
“…Agar diffusion assay of penicillins with Sarcina lutea as the test organism is preferred, as clavulanic acid does not inhibit this organism (Adam et al 1982;Schaad et al 1983;Witkowski et al 1982). Inhibition of the iJ-lactamase of a susceptible organism on penicillin-seeded medium is used as the microbiological assay for clavulanic acid and achieves a sensitivity of better than 0.2 mg/L (Adam et al 1982).…”
Section: Assay Methodsmentioning
confidence: 99%